Alkyne‐Protected AuPd Alloy Nanoparticles for Electrocatalytic Reduction of Oxygen. Issue 11 (3rd August 2015) - Deming, Christopher P.; Zhao, Albert; Song, Yang; Liu, Ke; Khan, Mohammad M.; Yates, Veronica M.; Chen, Shaowei
Abstract: Dodecyne‐capped AuPd alloy nanoparticles of varying compositions were prepared through the co‐reduction of metal‐salt precursors with NaBH4 . TEM measurements showed that the particles were largely in the range of 2–6 nm in diameter. XPS studies showed that the atomic Pd concentration varied from 65 to 100 %. Infrared spectroscopic measurements confirmed the bonding attachment of the dodecyne ligands on the nanoparticle surfaces, which rendered the nanoparticles readily dispersible in common organic media. Electrochemically, the resulting nanoparticles exhibited apparent catalytic activity in oxygen reduction with a volcano‐shaped variation with the metal composition. The best performance was identified with the sample composed of 91.2 at % Pd that exhibited a mass activity over eight times better than that of commercial palladium black, and almost twice as good in terms of specific activity. This remarkable performance was accounted for by both alloying with gold and surface functionalization with alkyne ligands that manipulated the electronic interactions between palladium and oxygen species. Abstract : Alloy protection : AuPd alloy nanoparticles exhibit apparent oxygen reduction reaction activity, owing to alloying and surface functionalization with alkyne ligands that manipulate the electronic interactions between palladium and oxygen species.